Genetical improvement of marine fish and shellfish : a french perspective - Boudry, Pierre; Chatain, Beatrice; Naciri-graven, Yamama; Lemaire, Christophe; Gerard, Andre (International Marine Biotechnology Conference, June 7-12, St John's, Newfoundland and Labrador, Canada, 1996)
In France, marine fish and shellfish farming is based mainly on the breeding of wild species, whose natural populations are traditionally exploited. Research programs are conducted by IFREMER, in co-operation with INRA and Universities. French research programs for the genetical improvement of marine fish and shellfish concern primarily seabass (Dicentrarchus labrax) and oysters (Ostrea edulis and Crassostrea gigas). The following programs are developed: •The knowledge of wild and farmed populations. The most recent prodjects involve the highly variable microsatellite markers. Seven markers are presently available for seabass and the work is now initiated on turbot (Scophthalmus maximus). In molluscs, microsatellite markers have been developed for the European flat oyster (O.edulis). • The control of sex-ratios. Research programs in physiology and developmental genetics are initiated in order to control sex-ratios in seabass. These programs include the production of gynogenetic progenies and the study of the sex-ratios of progenies issued from the crossing of hormonally feminised or masculinised breeders with normal ones. •The production of polyploids. Triploid seabass have been produced using high pressure and thermal shocks. The results after 6 months show a lower survival and growth compared with diploid controls. Triploid oysters, produced using chemical treatments (cytochalasin B or 6-DMAP), show better performances compared to diploids. •The establishment of breeding programs for traits of commercial interest. For marine fish, selection programs are initiated by industries and are scientifically supported by research institutes. The transfer to the industries is ensured by SYSAAF, a specialised structure that eases the adaptation of the professional network for t~e development of genetical improvement programs. In the fiat oyster, a breeding program for the resistance against Bonamia osteae has-been initiated in 1985 by IFREMER. Results show a better survival of selected populations compared with wild ...